Prevalence of Risky Sexual Behaviour and Associated Risk Factors Among Young Internally Displaced Persons in the Dschang Health District: A Mixed Method Study - Germaine Ndah Alombah,; Djam Chefor Alain,; Earnest Njih Tabah,; Ange Ariane Ghomsi Tadie,; Ifang Solomon Ndifon,; Gabriel Tchatchouang Mabou,; Noumedem Kenfack Jaures Arnaud, (Public Health, 2026)
Young internally displaced persons (YIDPs) face heightened vulnerability to risky sexual behaviours (RSB) due to displacement-related socioeconomic instability, disrupted education, limited access to sexual and reproductive health (SRH) services, and exposure to gender-based violence. Evidence on RSB among YIDPs in Cameroon remains scarce, particularly in humanitarian host communities. This study assessed the prevalence of risky sexual behaviours and identified associated factors among YIDPs aged 10–24 years in the Dschang Health District (DHD) in Cameroon. Methods: A community-based cross-sectional mixed-methods study was conducted between January and July 2025. Quantitative data were collected from 276 YIDPs selected using stratified systematic sampling across seven health areas. Data were analysed using SPSS version 27, with bivariate and multivariate logistic regression to identify predictors of RSB. Qualitative data were collected through four focus group discussions and four key informant interviews involving YIDPs, parents/guardians, teachers, community health workers, and SRH service providers. Thematic content analysis was performed to present quantitative findings. Results: The overall prevalence of RSB was 44.7% among all respondents and 90.4% among sexually active YIDPs. The most common RSBs were inconsistent or non-use of condoms (90.4%), unwanted pregnancy (47.3%), multiple sexual partnerships (35.6%), spontaneous sexual activity (33.3%), transactional sex, and substance use before sexual intercourse (26.7%). Multivariate analysis identified nightclub attendance more than once per month (aOR=5.01, p=0.001), psychoactive substance use (aOR=2.8, p=0.02), non-utlisation of SRH services (aOR=2.9, p=0.002), informal employment (aOR=2.2, p=0.03), and low economic status (aOR=2.5, p=0.038) as independent variables increasing the likelihood of RSB among YIPDs. Living with both parents reduced the likelihood of RSB (aOR=0.58, p=0.025). Qualitative findings highlighted peer pressure, economic difficulties, housing insecurity, misinformation about contraception, and coercion as key drivers of RSB. Conclusion: Risky sexual behaviours are highly prevalent among YIDPs in Dschang, driven by structural, social, and behavioural factors. Integrated, youth-friendly SRH interventions addressing economic vulnerability, substance use, and access to services are urgently needed in displaced populations.